In Vitro Inhibitory Effect of Silver Diamine Fluoride Combined with Potassium Iodide against Mixed-Species Biofilm Formation on Human Root Dentin - Jutharat Manuschai; Maki Sotozono; Shoji Takenaka; Niraya Kornsombut; Ryouhei Takahashi; Rui Saito; Ryoko Nagata; Takako Ida; Yuichiro Noiri (MDPI AG, 2024)
Applying a saturated potassium iodide (KI) solution immediately after silver diamine fluoride (SDF) application may affect the inhibitory effects of SDF on biofilm formation. This study compared the efficacy of 38% SDF with and without KI on preventing mixed-species biofilm formation on human root dentin surfaces and assessed ion incorporation into root dentin. The biofilms, composed of Streptococcus mutans, Lactobacillus rhamnosus, and Actinomyces naeslundii, were grown on specimen surfaces treated with either SDF or SDF + KI. After 24 h, the biofilms were evaluated using scanning electron microscopy, live/dead staining, adenosine triphosphate (ATP) assays, colony-forming unit (CFU) counts, and quantitative polymerase chain reaction. A Mann-Whitney U test was used to compare the results between the groups. Ion incorporation was assessed using an electron probe microanalyzer. The relative ATP content in the SDF + KI group was significantly higher than that in the SDF group (p < 0.05). However, biofilm morphology and the logarithmic reduction in CFUs and bacterial DNA were comparable across the groups. The SDF + KI treatment resulted in less silver and fluoride ion incorporation than that yielded by SDF alone. The inhibitory effects of SDF and SDF + KI on mixed-species biofilm formation were almost equivalent, although KI application affected the ion incorporation.